Lufotoarkæologi i Slesvig: En status. - Mauritsen, Esben Schlosser (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
In 2018, the aerial archaeological project Fortiden set fra Himlen ended. It marks the culmination of thirteen years of active aerial reconnaissance in the region of Slesvig. A brief history of the aerial archaeological actors and activities in Slesvig is presented. Many important sites have been detected, especially by St. Joseph and Stig Jensen. Their work has resulted in important excavations in e. g. Dankirke, Vilslev, and Råhede. In 2005, there was a renewed interest in the aerial archaeology in Slesvig and the author initiated two projects: one focused on investigating the Iron Age defensive earthworks of Olgerdiget and Æ Vold, and the other project focused on finding settlement sites dating to the Viking Age. In 2009, these projects were followed by Fortiden set fra Himlen, which carried out surveying in Slesvig and the North Frisian islands in particular. Altogether, 130 sites were detected in Slesvig between 2005 and 2018. Roughly half of them can be dated to a specific period ranging from early Iron Age to historic times. The highest intensity of finds was made on the island of Föhr with no less than 156 hectares of cropmarks. It is hard to predict when aerial reconnaissance will be resumed in Slesvig. Nonetheless, new tools such as LiDAR scans, orthophotos, and drones ensure that aerial archaeology will keep playing a role in the future.